Cultivation agrotechnologies of winter wheat varieties developed by the North Caucasus FRAC - L. R. Oganyan; F. V. Eroshenko; V. I. Kovtun; I. G. Storchak (Зерновое хозяйство России, 2023)
The problem of improving the sustainability and efficiency of grain production, increasing its gross quantity and improving quality is a key one for farmers in the Stavropol region. Due to the lack of financial resources for most agricultural producers, the problem is largely solved by selecting the most effective cultivation technology elements, including new highly productive varieties due to the agrotechnology. The purpose of the current study was to determine the effect of forecrops, the level of mineral nutrition, sowing dates and seeding rates on productivity, grain quality and economic efficiency of cultivating new winter wheat varieties developed by the FSBSI “North-Caucasus Federal Research Agricultural Center”. As a result of study carried out on winter wheat crops of various varieties developed by the FSBSI “North-Caucasus FRAC”, productivity of the varieties sown in weedfree fallow was 5.71 t/ha, which was 3.41 t/ha more than after cropped fallow. The application of mineral fertilizers contributed to productivity improvement of the varieties sown in weedfree fallow on 1.27 t/ha, and on 1.8 t/ha when sown after winter wheat on average during 2018–2021. The maximum grain yield was identified at the optimal sowing time in September 30 – October 5 (an average of 6.8 % more than at early and late time). Different seeding rates did not have a significant effect on productivity. Based on the estimation of the effect of winter wheat cultivation technologies on productivity, grain quality and economic efficiency of cultivation, there have been given agrotechnological characteristics of the new winter wheat varieties developed by the North-Caucasus FRAC.